THE ROLE OF FINANCIAL LITERACY, BEHAVIOR, TECHNOLOGY, AND ATTITUDE IN INVESTMENT INTENTION - Dede Sunaryo; Lena Erdawati (Universitas Muhammadiyah Tangerang, 2026)
Investment interest among university students is critical for early financial participation, yet remains underexplored in the context of multidimensional financial factors. This study aims to analyze the influence of financial literacy, financial Experience, financial Behavior, financial technology, and financial Attitude on investment interest, with an empirical focus on active undergraduate students at the Faculty of Economics and Business (FEB), Universitas Muhammadiyah Tangerang. A quantitative method was employed, using SPSS version 25 for analysis. Data were collected via online questionnaires distributed via Google Forms, using a Likert scale, from 97 respondents. The analysis included validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing using t-tests and F-tests. The findings reveal that, in part, financial literacy does not significantly affect investment interest, whereas financial Experience, financial Attitude, and financial technology each have a positive and significant effect. However, financial Behavior shows no significant partial effect. Simultaneously, all five variables together exert a significant influence on investment interest. This study provides empirical evidence from a student sample in a developing institutional context. It offers novelty by integrating five financial constructs, including financial technology, into a single investment-interest model that has rarely been tested collectively among active university students.